PENGARUH STRATEGI PROMOSI TERHADAP MINAT KONSUMEN (Studi Evaluasi Penjualan Kamar Hotel Mutiara Merdeka Pekanbaru) - Dewi, Bangun Ervina Sari; Sutisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The purpose of this research to find out how about the implementation promotion strategy (advertising, personal selling, public relation, sales promotion, and direct marketing) for achieve the room and to find out how the consumes’ interest about (liking, preference, and conviction)The population of this research is the consumers of Hotel Mutiara Merdeka Pekanbaru. The number of this samples are 100 people. It is taken by slovin’s formula. The search procedure of respondents performed by accidental – sampling. The research data is primary data whom uses questionnaires as the research instrument. The data analysis of the research is statistical analysis whom supported by SPSS program.Based on the result of this research that conducted by the researcher, she takes a conclusion that promotion effect (advertising, personal selling, public relation, sales promotion and direct marketing) towards consumer’s interest (liking, preference, and conviction) in Hotel Mutiara Merdeka Pekanbaru are agree, but some of the respondents answered disagree. Some of them disagree with public relation such as sponsoring, populist activities, and over coming problem that known by media, and some of the others disagree with consumers interest such as preference (red: discount or bonus )Key word : Promotion (Advertising, Personal Selling, Public Relation, Sales Promotion and Direct Marketing) and Consumer’s Interest (Liking, Preference, Conviction)